Analisis Kondisi Psikologis Anak dari Keluarga Tidak Utuh pada Siswa SMA PGRI Kupang - Lolang Maria Masi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to describe the psychological condition of children from incomplete families who study at SMA PGRI Kupang. The research used a quantitative approach with a total sample size of 45 students. The sample selection used purposive sampling method. The instrument used in this study was a questionnaire on the psychological condition of children from incomplete families. The data analysis technique used descriptive quantitative with the percentage to measure the psychological condition of the children.  The results of the research show that there were some effects on the psychological condition of children from incomplete families such as divorce from their parents, death of family members, living separately, empty families, alcoholic families and quarrelsome parents which reached 63%. It means that the family which was not intact was categorized as having a high effect on the students’ psychological condition, such as feeling sad, rejected, angry, hurt, lonely, guilty and blaming themselves, anxious, depressed, shutting down, embarrassed, stressed, feeling insecure and losing affection. Therefore, the supervising teachers can provide motivation and provide Counseling Guidance services for every student, especially those who live in the intact families for their achievement and their improvement at the Middle Education level.